Graduate Programs in Medical Informatics at the Paris Universities - Degoulet, Patrice; Venot, Alain; Auvert, Bertran; Grémy, François (Yearbook of Medical Informatics, 1995)
Most medical schools in France have chairs in Biostatistics and Medical Informatics to coordinate the teaching of these two disciplines both within the regular curriculum of the medical studies and as a specialized teaching. This paper describes the current medical informatics specialized program offered at the Paris Universities. Since 1968 the program has comprised a Master of Science and a Ph.D. degree. At the Master Level, despite several reforms and in-depth program revisions the curriculum is still organized as a set of modules of 100 hours teachins with a large freedom for the medical faculties to define the contents of the courses and for the students to organize their studies and combine medical informatics, biomathematics and biostatistics training. Since 1990, an intensive one-year full-time course is offered, called Advanced Study Diploma in Medical Informatics, which is strongly research oriented. This program seems a good strategy to form medical informatics special1 ists who have initially received a broader education in informatics and statistics.